ANALISIS KETERAMPILAN DASAR MENGAJAR GURU DI SMA CENDANA PEKANBARU - Nova Ira Wahyuni; Syakdanur Nas; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The aim of the research was to explore teaching skills of teachers at senior high school of Cendana, Pekanbaru. Those teaching skills covered (1) opening skills; (2) questioning skills; (3) reinforcement skills; (4) variations skills; (5) explaining skills; (6) the skills to small group discussions; (7) classroom management skills;       (8) individual learning skills; and (9) closing skills.  The population in this study were all teachers of senior high school of Cendana, Pekanbaru, totality 45 people. The primary data was collected using anquote to 39 respondents. The data collected, then, was analysed using descriptive technique. The results of this study showed that the average level of teaching skills of teachers in senior high school of Cendana, Pekanbaru was 86,91% and the average skills level of teachers to teach Economics at senior high school of Cendana, Pekanbaru was 2,99. Keyword : Teaching Skills